Mitochondrial DNA alteration in primary and metastatic colorectal cancer: Different frequency and association with selected clinicopathological and molecular markers - Britta Kleist; Thuja Meurer; Micaela Poetsch (Tumor Biology)
This study attempts to determine whether primary tumor tissue could reliably represent metastatic colorectal cancer in therapy-guiding analysis of mitochondrial microsatellite instability. Therefore, we investigated the concordance of microsatellite instability in D310, D514, and D16184 (mitochondrial DNA displacement loop), and its association with selected clinical categories and KRAS/NRAS/BRAF/PIK3CA/TP53 mutation status between primary and metastatic colorectal cancer tissue from 119 patients. Displacement loop microsatellite instability was significantly more frequently seen in lymph node metastases (53.1%) compared to primary tumors (37.5%) and distant metastases (21.4%) ( p  = 0.0183 and p  = 0.0005). The discordant rate was significantly higher in lymph node metastases/primary tumor pairs (74.6%) than in distant metastases/primary tumor pairs (52.4%) or lymph node metastases/distant metastases pairs (51.6%) ( p  = 0.0113 and p  = 0.0261) with more gain (86.7%) than loss (61.1%) of microsatellite instability in the discordant lymph node metastases ( p  = 0.0024). Displacement loop instability occurred significantly more frequently in lymph node metastases and distant metastases of patients with early colorectal cancer onset age <60 years ( p  = 0.0122 and p  = 0.0129), was found with a significant high rate in a small cohort of TP53 -mutated distant metastases ( p  = 0.0418), and was associated with TP53 wild-type status of primary tumors ( p  = 0.0009), but did not correlate with KRAS , NRAS , BRAF , or PIK3CA mutations. In conclusion, mitochondrial microsatellite instability and its association with selected clinical and molecular markers are discordant in primary and metastatic colorectal cancer, which could have importance for surveillance and therapeutic strategies.